The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/yco.0b013e3283577ed1
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric syndromes in Parkinson's disease

Abstract: Standardized criteria should be used to diagnose depression and apathy in Parkinson's disease. Psychotherapy and pharmacotherapy are useful treatment modalities for affective disorders in Parkinson's disease. Clozapine is still the most effective, albeit rarely used, treatment for psychosis in Parkinson's disease. Impulse control disorders are relatively frequent in Parkinson's disease and all patients should be screened for this complex disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 29 publications
1
34
0
3
Order By: Relevance
“…Stemming from a progressive loss of dopaminergic neurons in the substantia nigra, motor symptoms mainly encompass bradykinesia, rigidity, and tremor (Damier, Hirsch, Agid, & Graybiel, 1999). Frequent additional nonmotor symptoms include depression, anxiety, apathy, (hypo‐)mania, dementia, psychosis, and impulse control disorder (Callesen, Weintraub, Damholdt, & Moller, 2014; van der Hoek et al., 2011; Maier et al., 2014; Reijnders, Ehrt, Weber, Aarsland, & Leentjens, 2008; Richard, 2007; Riedel et al., 2008; Sagna, Gallo, & Pontone, 2014; Starkstein, Brockman, & Hayhow, 2012). Together with motor symptoms (Appleman, Stavitsky, & Cronin‐Golomb, 2011; Hechtner et al., 2014; Weintraub et al., 2010), nonmotor symptoms can severely affect patients′ health‐related quality of life (Montel, Bonnet, & Bungener, 2009; Shearer, Green, Counsell, & Zajicek, 2012; for reviews see Den Oudsten, Van Heck, & De Vries, 2007; van Uem et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Stemming from a progressive loss of dopaminergic neurons in the substantia nigra, motor symptoms mainly encompass bradykinesia, rigidity, and tremor (Damier, Hirsch, Agid, & Graybiel, 1999). Frequent additional nonmotor symptoms include depression, anxiety, apathy, (hypo‐)mania, dementia, psychosis, and impulse control disorder (Callesen, Weintraub, Damholdt, & Moller, 2014; van der Hoek et al., 2011; Maier et al., 2014; Reijnders, Ehrt, Weber, Aarsland, & Leentjens, 2008; Richard, 2007; Riedel et al., 2008; Sagna, Gallo, & Pontone, 2014; Starkstein, Brockman, & Hayhow, 2012). Together with motor symptoms (Appleman, Stavitsky, & Cronin‐Golomb, 2011; Hechtner et al., 2014; Weintraub et al., 2010), nonmotor symptoms can severely affect patients′ health‐related quality of life (Montel, Bonnet, & Bungener, 2009; Shearer, Green, Counsell, & Zajicek, 2012; for reviews see Den Oudsten, Van Heck, & De Vries, 2007; van Uem et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde PH'na eşlik eden depresif bozukluk tedavisinde trisiklik antidepresanlar, selektif serotonin geri alım inhibitörleri ve psikoterapinin etkin olduğu belirtilmektedir 8 .…”
Section: Introductionunclassified
“…Several studies have also shown that individuals with depression are 2.2 to 3.2 times more likely to develop PD compared to healthy controls 43 . Although the available data regarding this correlation are less conclusive than for hyposmia and RBD, the onset of depressive symptoms may precede the motor signs, with a peak around 3-6 years before the diagnosis of PD.…”
Section: Behavioral Disordersmentioning
confidence: 99%
“…Non-motor signs: prevalence, respective level of functional disability and potential role as premotor signs of Parkinson's disease 15,16,17,18,19,35,43,44,45,47,48,49,51,52,53,60 . healthy elderly individuals, those with proven olfactory deficit had a higher risk of developing symptomatic PD clinical and when they remained asymptomatic, these individuals presented LB in the SNc on post-mortem examination.…”
Section: Olfactory Deficitmentioning
confidence: 99%